Integrated Maintenance Planning in Manufacturing Systems - Al-Turki, Umar M.; Ayar, Tahir; Yilbas, Bekir Sami.; Sahin, Ahmet Ziyaettin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book introduces the concept of integrated planning for maintenance and production taken into account quality and safety for high global socio-economic impact. It provides insight into the planning process at a global level starting from the business level and ending with the operational level where the plan is implemented and controlled.
Introduction -- Maintenance in Manufacturing Environment: An Overview -- Integrated Maintenance Planning -- Health, Safety and Sustainability in Maintenance -- Ethics in Maintenance -- Recent and Future Trends in Maintenance.
Keywords: Engineering; Organization; Planning; Production management; Quality control; Reliability; Industrial safety; Engineering; Quality Control, Reliability, Safety and Risk; Operations Management; Organization; Electronic books